Trends of stage, grade, histology and tumour necrosis in renal cell carcinoma in a European centre surgical series from 1984 to 2010. Issue 8 (25th May 2012) - Pichler, Martin; Hutterer, Georg C; Chromecki, Thomas F; Jesche, Johanna; Kampel-Kettner, Karin; Eberhard, Katharina; Hoefler, Gerald; Pummer, Karl; Zigeuner, Richard
Abstract : Aims: To analyse renal cell carcinoma (RCC) stage, grade, histology and necrosis migration in a large European centre series over the last 27 years. Methods: The pathology reports of 2739 consecutive patients with RCC who underwent nephrectomy from 1984 to 2010 at the institution of the authors were systematically re-evaluated. Patients were pooled into five time groups according to the date of surgery: group 1: 1984–1989, group 2: 1990–1994, group 3: 1995–1999, group 4: 2000–2004 and group 5: 2005–2010, respectively. Changes in pT categories according to WHO 2010 classification, tumour grade, histological subtype and presence of tumour necrosis (TN) were evaluated. Results: Small pT1a tumours were found in 62/485 (12.8%) and 312/639 (48.8%) patients in groups 1 and 5, respectively (p<0.001). Advanced tumour stages (pT3a-4) were found in 306/485 (63.1%) and 171/639 (26.8%) patients in groups 1 and 5, respectively (p<0.001). The number of grade 3/4 tumours increased from 62/485 (12.7%) and 130/639 (20.3%) in groups 1 and 5, respectively, whereas the number of grade 1 tumours decreased over time (p<0.001). There has been a significant histological migration for the chromophobe subtype from 1.1% to 4.3% (p=0.002). The frequency of the presence TN decreased from 41.7% in group 1 to 32.7% in group 5 (p<0.001). Conclusions: In contrast to data from Australia but similar to data from US cohorts, a statistically significant stage migration towards small RCCs was observed in this European cohort. Significant changes in tumour grade, histological subtype and TN were also observed.